Attachment & sexuality - Lichtenberg, Joseph D.; Blatt, Sidney J. (Sidney Jules), 1928-2014.; Diamond, Diana, 1948- (New York : Analytic Press, 2007)
Publisher description
Attachment and sexuality / Morris Eagle -- A behavioral systems perspective on the psychodynamics of attachment and sexuality / Mario Mikulincer and Phillip R. Shaver -- Attachment and sexuality during adolescence : interaction, integration, or interference / Massimo Ammaniti, Giam[paolo Nicolais, and Anna Maria Speranza -- When sexuality reaches beyond the pleasure principle : attachment, repetition, and infantile sexuality / Lissa Weinstein -- Sense and sensuality : hedonic intersubjectivity and the erotic imagination / Jeremy Holmes --
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Parent and child; Sex (Psychology); Interpersonal relations; Object relations (Psychoanalysis); Object Attachment; Parent-Child Relations; Sexuality -- psychology; Electronic books